USE OF ELECTRICAL RESISTIVITY FOR MAPPING THE LEACHATE DISTRIBUTION IN BLANG BINTANG SANITARY LANDFILL, ACEH DISTRICT - Zakia Masrurah; Akmal Muhni; Muhammad Yanis; Muzakir Zainal (Indonesian Physical Review, 2026)
An increase in waste in urban areas, especially in landfills, can produce leachate that has the potential to pollute the environment. The Blang Bintang waste treatment facility, which uses a sanitary landfill system, is in a hilly area with complex geology dominated by andesite volcanic rocks. This study aims to identify and estimate the level of leachate contamination at the Blang Bintang landfill in Aceh using Electrical Resistivity Tomography (ERT).  Four ERT profiles were measured in the leachate treatment facility area, spanning 180 meters in length and up to 30 meters in depth. ERT data analysis using the Res2dinv software produced an accurate model with an RMS error of 10%-20%. The modeling results indicate the presence of conductive zones (5–150 Ohm.m) near the surface layers of profiles 1 and 2, suggesting leachate contamination. The electrical resistivity tomography (ERT) model further demonstrates leachate accumulation in the subsurface, which poses a potential risk to groundwater quality. In Profile 3, conductive zones (5–200 Ohm.m) are observed along the underground leachate pipeline. For Profile 4, conductive layers (15–250 Ohm.m) are attributed to seepage from the first leachate pond, indicating substantial contamination. This study provides landfill managers with valuable data on subsurface contamination that cannot be identified from surface observations. It also advances geophysical methods for environmental impact assessments.